Blood composition of the reindeer . II. Blood chemistry - Nieminen, Mauri; Timisjärvi, Jouni (Rangifer, 1983)
The blood chemical composition of 578 semi-domestic reindeer were investigated in respect to age, season, calving and nutrition in Northern Finland during 1973-79. The weight gain was maximally 400 g/day at an age of 4-8 weeks as also reflected by high serum thyroxine (T4), alkaline phosphatase (SAP), creatine phosphokinase (CPK) and blood glucose values. Low SAP activity in winter indicated a cessation of growth. The pH of the venous blood was 7.35 and the clotting activity very high (21 sec, 100 %) in summer and autumn. 15 protein bands and 15 fatty acids were discernible in reindeer serum. The total serum protein was 58 g/1 in the 20-day-old calf and 87 g/1 in adult hind in the autumn, the difference being caused by changes in globulins. The neonatal fluctuation of immunoglobulins suggests that the calf acquires its passive immunity soon after birth by the intestinal absorption of proteins and that its endogenous synthesis of gamma globulins begins in the 4th week of life. The serum total lipids (2.9 g/1), triglycerides (0.29 mmol/1) and cholesterol (1.6 mmol/1) were low in newborn calves and reached their adult levels at the age of 5 months (average 5.1 g/1, 0.4 mmol/1, 2.7 mmol/1, respectively). The young calves had higher serum cholesterol, total and free fatty acid, myristic acid and palmitic acid, but lower stearic and oleic acid values than adult hinds. The reindeer calf liberates considerable amounts of catecholamines during the first days after birth, but the postpartum dopamine-B-hydroxylase activity was rather low. The means of blood glucose (3.4-4.6 mmol/1), total serum proteins (63 - 87 g/1), albumin (39 - 43 g/1), total globulins (23 - 44 g/1), urea (5.7-9 mmol/1), total lipids (2.7 - 5.2 g/1), triglycerides (0.17 - 0.33 mmol/1), total fatty acids (0.89 - 1.54 g/1), calcium (2.2 - 2.6 mmol/1), inorganic phosphorus (1.6 - 2.2 mmol/1), magnesium (0.8 - 1.2 mmol/1) and copper (6.7 - 18 |Jmol/l) of free-grazing adult hinds were highest in summer and autumn and decreased during winter. The lowest means were measured for the starved hinds in early spring. The high serum urea and CPK, LDH and SAP activities reflected catabolism of the body proteins and tissue breakdown during starvation. Season and nutrition did not affect serum T4, creatinine, sodium and chloride values. High body weight and blood chemical values were measured for the hinds fed on silage and molasses in winter. Poron veri. II. Veren kemia. Abstract in Finnish / Yhteenveto: 578 puolivillin poron veren kemiallista koostumusta tutkittiin iån, vuodenajan, vasonnan ja ravitsemustilan suhteen vuosina 1973-79. Painon lisays oli suurimmillaan 400 g/vrk 4-8 viikon iassa ja sita kuvastivat myos korkeat seerumin tyroksiinin (T4), alkaalisen fosfataasin (SAP), kreatiinifosfokinaasin (CPK) ja veren sokerin arvot. Alhainen SAP aktiivisuus talvella osoitti kasvun pysahtymistå. Laskimoveren pH oli 7.35 ja veren hyytymiskyky (21 sek, 100 %) erittåin hyvå kesålla ja syksylla. Seerumista erotettiin 15 eri valkuaista ja 15 rasvahappoa. Seerumin valkuaisainepitoisuus oli 58 g/l 20 vrk:n iassa ja vaatimilla 87 g/l syksylla. Ero johtui globuliinien måaran muutoksesta. Immunoglobuliinien muutokset osoittavat, etta syntymanjålkeisen vastustuskykynså vasa saa ilmeisesti emån maidosta ja etta oma gammaglobuliinien tuotanto alkaa vasta 4 viikon iåsså. Vastasyntyneen vasan seerumin lipidit (2,9 g/l), triglyseridit (0,29 mmol/1) ja kolesteroli (1,6 mmol/1) olivat melko alhaiset ja saavuttivat aikuisen tason 5 kuukauden iassa (keskimåarin 5,1 g/l, 0,4 mmol/1, 2,7 mmol/1, vastaavasti). Vasojen seerumin kolesteroli-, kokonaisrasvahappo-, myristiinihappo- ja palmitiinihappopitoisuudet olivat korkeammat, mutta steariinihappo- ja oljyhappopitoisuudet alhaisemmat kuin vaatimilla. Ensimmaisinå vuorokausina vasa tuottaa runsaasti katekolamiineja, mutta seerumin dopamiini-B-hydroksylaasin aktiivisuus on melko alhainen. Vapaana laiduntavan vaatimen veren sokeri (3,4 - 4,6 mmol/1), seerumin kokonaisvalkuainen (63 - 87 g/l), albumiini (39 - 43 g/l), globuliinit (23 - 44 g/l), urea (5,7 - 9 mmol/1), kokonaislipidit (2,7 - 5,2 g/l), triglyseridit (0,17 - 0.33 mmol/1), rasvahapot (0,89 - 1,54 g/l), kalsium (2,2 - 2,6 mmol/1), fosfori (1,6 - 2,2 mmol/I), magnesium (0,8 - 1,2 mmol/1) ja kupari (6,7-18 (Jmol/l) olivat korkeimmillaan kesallå ja syksylla ja laskivat talvella. Alhaisimmat pitoisuudet mitattiin nålkiintyneille vaatimille kevaalla. Seerumin korkeat ureapitoisuudet ja CPK, LDH ja SAP aktiivisuudet kuvastivat kehon valkuaisten ja kudosten hajoamista nalkiintymisen aikana. Vuodenajoilla ja ravinnolla ei ollut vaikutusta seerumin T4-, kreatiniini-, natrium- ja kloridipitoisuuksiin. Korkeat ruumiinpainot ja veren kemialliset arvot mitattiin vaatimille, joita ruokittiin sailorehulla ja melassileikkeellå talvella. Renblod. II. Blodkemi. Abstract in Swedish / Sammandrag: Den kemiska sammansattningen av blodet hos 578 halvvilda vajor undesoktes under år 1973 — 1979 med hanvisning till ålder, årstid, kalvning och nåringstillstånd. Viktokningen var storst, 400 g/dygn, vid en ålder av 4 — 8 veckor. Detta återspeglades aven i de hoga varden av serumthyroxin (TV), alkalfosfatas (SAP), kreatininfosfokinas (CPK) och i blodsockerhalten. Den låga SAP-aktiviteten under vintern var ett tecken på att tillvåxten stannat. Vårdet av pH i venblodet var 7,46 och koagulationskapaciteten (21 sek, 100%) var mycket hog under sommaren och hosten. 15 olika åggviteåmnen och 15 fettsyror skiljdes ur serum. Halten av åggviteåmnen i serum var 58 g/1 vid en ålder av 20 dygn och 87 g/1 hos vajorna på hosten. Skillnaden berodde på forandringen i globulinmångden. Foråndringarna hos immunoglobulinerna påvisar, att kalven får sin motståndsformåga efter fodseln ur vajans mjolk och att kalven sjålv borjar producera gammaglobuliner forst då den nått en ålder av 4 veckor. Den nyfodda kalvens serumlipider (2,9 g/1), triglycerider (0,29 mmol/1), och kolesterol (1,6 mmol/1) var tåmligen låga och uppnådde nivån hos en vuxen ren vid 5 månaders ålder (respektive medeltal 5,1 g/1, 0,4 mmol/1, 2,7 mmol). Halterna av kolesterol, fettsyra, myristinsyra och palmitinsyra var hogre i kalvarnas serum, emedan halterna av stearinsyra och oljesyra var lagre ån hos vajor. Under de forstå levnadsdygnen producerar kalven katekolaminer i rikliga mångder. Dåremot år serumdopamid - B - hydroxylas-aktiviteten ganska låg. En fritt betande vajas blodsockerhalt (3,4 - 4,6 mmol/1), totalåggvitehalt i serum (63 - 87 g/1), albuminhalt (39 - 43 g/1), globulinhalt (23 - 44 g/1), urea (5,7- 9 mmol/1), totala lipidhalt (2,7 - 5,2 g/1), triglyceridhalt (0,17-0,33 mmol/1), fettsyrehalt (0,89 - 1,54 g/1), kalciumhalt (2,2 - 2,6 mmol/1), fosforhalt (1,6 - 2,2 mmol/1), magnesiumhalt (0,8 - 1,2 mmol/1) och kopparhalt (6,7 - 17 )Jmol/l) var hogst under sommaren och hosten emedan de sjonk under vintern. De lågsta halterna mattes hos u-tsvultna vajor på våren. Den hoga ureahalten i serum samt CPK-, LDH- och SAP-aktiviteterna återspeglar åggviteåmnens och våvnaders upplosning i kroppen. Årstiderna och nåringen inverkade varken på halterna av T4 kreatinin, natrium eller klorid i serum. De hoga siffrorna for kroppsvikt och blodets kemiska varden mattes hos vajor som under vintersåsongen matats med pressfoder och melassflis.